TYPES OF IḌĀFAH AND THEIR APPROACHES IN CLASSICAL ARABIC AND MODERN STANDARD ARABIC: A COMPARATIVE HISTORICAL LINGUISTIC STUDY | أنواع الإضافة وطرائق تناولها بين العربية الكلاسيكية والعربية الفصحى الحديثة: دراسة لغوية مقارنة تاريخية - Zuhriyyatul Athiroh; Muhammad Syamsul Arifin; Ahmed Salim Moosa Alkharusi (Al Ibrah: Journal of Arabic Language Education, 2026)
This study investigates the phenomenon of iḍāfah (genitive construct) in Arabic from a comparative-historical (diachronic) perspective. It aims to analyze the types of iḍāfah in Classical Arabic and Modern Standard Arabic (MSA), to examine how each period approaches these types, and to identify similarities and differences between them. The study employs library research and comparative-historical linguistic analysis, drawing on six purposively selected primary sources  three classical (al-Zajjājī, Ibn Ājurrūm, Ibn Mālik) and three MSA (Caspari, Ryding, Badawi et al.). Data analysis followed the diachronic comparative method via Verhaar and Hopper-Traugott’s framework as elaborated by Crowley and Bowern. Both periods agree on two fundamental types: iḍāfah maʿnawiyyah and iḍāfah laḏẓiyyah. However, Classical Arabic employs systematic, detailed exposition with subcategories, while MSA adopts a descriptive-communicative orientation prioritizing functional usage. This difference is classified as Substitution in Hopper and Traugott’s theory, indicating a shift in analytical perspective rather than disappearance of the grammatical category. This study contributes to Arabic comparative linguistics by bridging classical and modern traditions.تتناول هذه الدراسة ظاهرةَ الإضافة في اللغة العربية من منظور مقارن-تاريخي ديكروني، إذ تهدف إلى تحليل أنواع الإضافة وطرائق تناولها في العربية الكلاسيكية والعربية الفصحى الحديثة. اعتمدت الدراسة منهجين هما البحث المكتبي والدراسة اللغوية المقارنة-التاريخية، مستندةً إلى ستة مصادر أولية ثلاثة منها تمثّل العربية الكلاسيكية وثلاثة تمثّل العربية الفصحى الحديثة. وتوصّلت الدراسة إلى أن كلا الفترتين تتّفقان على تقسيم الإضافة إلى نوعين أساسيين: الإضافة المعنوية والإضافة اللفظية. غير أنهما تختلفان في أسلوب التناول: إذ تميل العربية الكلاسيكية إلى العرض التفصيلي المنهجي، بينما تميل العربية الفصحى الحديثة إلى التوجّه الوصفي التواصلي. وصُنِّف هذا الاختلاف ضمن فئة الاستبدال وفق نظرية هوبر وتراوغوت